Infestation of a Complementary Food by Tribolium Castaneum Herbst Macleay 1825 (Coleoptera: Tenebrionidae) - Ardjoune Adji, Fatimé; Tinkeu L.S, Ngamo (International Journal of Scientific Research and Management (IJSRM), 2018)
During storage of complementary foods in the form of flour, secondary pests attacked including T. castaneum. To evaluate these depreciation two formulations were elaborated using infested insects in 1200 ml jars with 11 repetitions for each. After 90 days of infestation, emergences were noted. The average sizes of the different stages showed that the formulation with bambara groundnut was that which noted the most emergences. The average of stage I is 68.4 ± 26.3 in the formulation with bambara groundnut and 29.2 ± 14.1 in that without. The same is true for stage V and in the adults where the emergences respectively were 111.9 ± 45.3 and 397.2 ± 130.6 in formulation with bambara groundnut and 46.8 ± 15.6 and 164.7 ± 22.5 in the formulation without